Checks and balances: Enforcing constitutional constraints - Randall G. Holcombe (Economies, 2018)
Constitutional political economy has focused heavily on designing constitutional rules sufficient to constrain governmental power. More attention has been devoted to designing rules that are effective constraints than on the institutions that would be required to enforce them. One problem is that rules are interpreted and enforced by the political elite, who tend to interpret and enforce them in ways that favor their interests over those of the masses. Democratic oversight is ineffective because voters realize they have no influence over public policy, and are therefore rationally ignorant. A system of checks and balances within government is necessary for enforcing constitutional constraints because it divides power among elites with competing interests and enables one group of elites to check the power of others. Checks and balances within governmental institutions are necessary to constrain the government from abusing its power.
Keywords: H11; 330; constitutional constraints; checks and balances; political elite; democratic oversight